(untitled) (Stato, Chiese e pluralismo confessionale, 2021)
SOMMARIO: 1. Una premessa. I cattolici nella vita politica e la condanna dell’aborto nel magistero della Chiesa - 2. Il precedente del 2004 e la conseguente dichiarazione dell’Episcopato statunitense - 3. L’interpretazione del can. 915 nei suoi elementi costitutivi: la categoria degli “aliique in manifesto gravi peccato obstinate perseverantes” - 4. Un’applicazione concreta: il decreto episcopale del 2019 alla luce del canone (e viceversa). «Ad Sacram Communionem ne admittantur»: can. 915 and Catholic politicians who promote abortion in the light of a Bishop’s recent decree ABSTRACT: Moving from a 2019 decree by the Bishop of Springfield in Illinois, the present contribution aims to analyze the nature, the requirements and the implications of can. 915 CIC, which concerns the circumstances of non-admission of the faithful to Holy Communion, namely in order to understand whether the case of politicians supporting legislations that promote abortion falls into the category of those who “obstinately persevere in manifest grave sin”.